Neue Arten der Gattung Mescirtes MOTSCHULSKY, 1863 aus Laos und Vietnam (Coleoptera, Scirtidae) (190. Beitrag zur Kenntnis der Scirtidae). - Klausnitzer, Bernhard (Contributions to Entomology = Beiträge zur Entomologie, 2013)
One new species of Mescirtes Motschulsky, 1863 from Laos and a second from Vietnam are described. M. sedlagi n. sp. is mainly characterized by its distinctive colouration. M. eberti n. sp. is compared with M. rutilicollis Klausnitzer, 2012. Identification keys for males and females of the species known from Southeast Asia (mainland) and a catalog of all Mescirtes are presented.KeywordsColeoptera, Scirtidae, Mescirtes, new species, determination key, Laos, Vietnam, Oriental Region.Nomenclatural Actseberti Klausnitzer, 2013 (Mescirtes), spec. nov.sedlagi Klausnitzer, 2013 (Mescirtes), spec. nov.